2010
DOI: 10.2135/cropsci2009.08.0463
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Hybrid Influences on Food‐Grade Sorghum Grain Yield and Hardness

Abstract: Few studies have examined grain quality of food‐grade sorghum hybrids. The objective of this study was to determine the effects of environment and hybrid on grain quality of commercially available food‐grade sorghums. A randomized complete block experiment with three replications was planted in 12 environments, which included the 2004 and 2005 growing seasons and irrigated and dryland water regimes in eastern, central, and west central Nebraska and a dryland low‐N environment in eastern Nebraska. Environment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 36 publications
7
23
2
Order By: Relevance
“…Maize samples treated with low irrigation levels had significantly lower test weight than those treated with high irrigation levels (Fig. 1C), which was in agreement with results reported by Griess et al (2010) for sorghum grain. True density of maize samples decreased as irrigation level decreased (Fig.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 90%
See 1 more Smart Citation
“…Maize samples treated with low irrigation levels had significantly lower test weight than those treated with high irrigation levels (Fig. 1C), which was in agreement with results reported by Griess et al (2010) for sorghum grain. True density of maize samples decreased as irrigation level decreased (Fig.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 90%
“…True density of maize samples decreased as irrigation level decreased (Fig. 1D), which was in contrast with research on sorghum (Griess et al 2010). No relationship between kernel density and breakage susceptibility was found, which agreed with some previous studies (Bauer and Carter 1986;Kniep and Mason 1989).…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 87%
“…1 grade sorghum (0.73 g cm -3 ) (USDA, 2008). Sorghum samples treated with high irrigation levels had a higher test weight than those treated with low irrigation levels, which agrees with the results reported by Griess et al (2010). True density of sorghum samples was not affected by irrigation level, which agrees with the research on sorghum (Griess et al, 2010).…”
Section: Physical Properties and Chemical Compositionsupporting
confidence: 90%
“…Griess et al (2010) reported similar results: sorghum starch concentration under irrigated conditions was significantly higher than under dryland conditions. Figure 1 shows a strong linear relationship between total starch contents and ethanol yield (R 2 = 0.96, p < 0.0001), which agrees with the previous research reported by Wu et al (2008), Lacerenza et al (2008), and Yan et al (2011).…”
Section: Physical Properties and Chemical Compositionsupporting
confidence: 57%
See 1 more Smart Citation